2022
DOI: 10.3390/jfb13010004
|View full text |Cite
|
Sign up to set email alerts
|

Surface Functionalization of Poly(l-lactide-co-glycolide) Membranes with RGD-Grafted Poly(2-oxazoline) for Periodontal Tissue Engineering

Abstract: Bone tissue defects resulting from periodontal disease are often treated using guided tissue regeneration (GTR). The barrier membranes utilized here should prevent soft tissue infiltration into the bony defect and simultaneously support bone regeneration. In this study, we designed a degradable poly(l-lactide-co-glycolide) (PLGA) membrane that was surface-modified with cell adhesive arginine-glycine-aspartic acid (RGD) motifs. For a novel method of membrane manufacture, the RGD motifs were coupled with the non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…[ 33 ] These results suggest that the mannose moieties decorating the surface of the PLGA‐POx‐Man NP presented a favorable interaction with the mannose receptors when compared to those available at the surface of the PLGA‐PEG‐Man NP. This may be due to a decrease in the interfacial tension between the PLGA‐based NP surface and the surrounding aqueous environment, caused by the POx coating, as previously shown by Tryba et al., [ 33 ] allowing for active targeting and a more extensive internalization by APC.…”
Section: Discussionmentioning
confidence: 99%
“…[ 33 ] These results suggest that the mannose moieties decorating the surface of the PLGA‐POx‐Man NP presented a favorable interaction with the mannose receptors when compared to those available at the surface of the PLGA‐PEG‐Man NP. This may be due to a decrease in the interfacial tension between the PLGA‐based NP surface and the surrounding aqueous environment, caused by the POx coating, as previously shown by Tryba et al., [ 33 ] allowing for active targeting and a more extensive internalization by APC.…”
Section: Discussionmentioning
confidence: 99%
“… 41 Moreover, the peak at 1647 cm −1 was intensified, which may be due to the superimposed vibration of H 2 O and an amide I band that is mainly associated with the C=O stretching vibration. 42 , 43 Although the spectra of ASA@tHALLG showed no obvious difference from that of tHALLG, these results suggested that the GCP assembly was successfully covalently bonded on the surface of tHA, which was further confirmed by XPS investigation. As shown in Figure 2C , apart from major atomic elements carbon, oxygen, calcium, and phosphorus, a weak nitrogen peak at 399 eV was recorded in the tHA nanocomposite, suggesting the presence of pDA.…”
Section: Resultsmentioning
confidence: 65%
“…Table contains the quantitative data of the C 1s fit, and Figure depicts the actual C 1s curve fittings. Based on the literature and the molecular structure of PCL/PLGA, the copolymer’s C 1s envelope can be fitted into 3 different peaks: a peak at 285 eV corresponding to carbon and hydrocarbon bonds (C–H/C–C), a peak at 286.5 eV accredited to hydroxyl groups (C–O) and a peak at 289.1 eV ascribed to carboxyl groups (O–CO). , A good C 1s curve fit of the untreated sample using these 3 peaks could be indeed performed. The relative concentrations of these peaks on the inner and outer walls primarily featured the chemical structure of PCL with a small increase in the C–O and O–CO bond concentrations due to the presence of PLGA as the smallest portion of the blended electrospinning solution used for the nanofibers biofabrication.…”
Section: Resultsmentioning
confidence: 99%